Imaging of Endocytic Trafficking and Extracellular Vesicles Released Under Neratinib Treatment in ERBB2+ Breast Cancer Cells. (July 2021) - Santamaria, Sara; Gagliani, Maria Cristina; Bellese, Grazia; Marconi, Silvia; Lechiara, Anastasia; Dameri, Martina; Aiello, Cinzia; Tagliatti, Erica; Castagnola, Patrizio; Cortese, Katia
Breast cancers (BCa) with ERBB2 amplification show rapid tumor growth, increased disease progression, and lower survival rate. Deregulated intracellular trafficking and extracellular vesicle (EVs) release are mechanisms that support cancer progression and resistance to treatments. Neratinib (NE) is a Food and Drug Administration–approved pan-ERBB inhibitor employed for the treatment of ERBB2 + BCa that blocks signaling and causes survival inhibition. However, the effects of NE on ERBB2 internalization, its trafficking to multivesicular bodies (MVBs), and the release of EVs that originate from these organelles remain poorly studied. By confocal and electron microscopy, we observed that low nanomolar doses of NE induced a modest ERBB2 internalization along with an increase of clathrin-mediated endocytosis and of the CD63+ MVB compartment in SKBR-3 cells. Furthermore, we showed in the culture supernatant two distinct EV subsets, based on their size and ERBB2 positivity: small (30–100 nm) ERBB2 − EVs and large (>100 nm) ERBB2 + EVs. In particular, we found that NE increased the overall release of EVs, which displayed a reduced ERBB2 positivity compared with controls. Taken together, these results provide novel insight into the effects of NE on ERBB2 + BCa cells that may lead to a reduction of ERBB2 potentially transferred to distant target cells by EVs: